2023
DOI: 10.3389/fpubh.2023.1135964
|View full text |Cite
|
Sign up to set email alerts
|

Depression and suicidal ideation among individuals with type-2 diabetes mellitus, a cross-sectional study from an urban slum area of Karachi, Pakistan

Abstract: BackgroundSuicidal thoughts and depression are associated with patients with diabetes, especially patients with low socioeconomic backgrounds and prolonged illness.ObjectiveWe aimed to estimate suicidal thoughts and depression among patients with type 2 diabetes (T2D) in the slums of Karachi.MethodsThis cross-sectional study was conducted across 38 locations in the slums of Karachi to understand depression, suicidal thoughts, and other supporting factors of depression associated with T2D. The three-item Oslo S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…This finding further aligns with prior research that found high rate of depressive symptoms individual with T1D, which were linked to their diabetes related distress 24 . Finally, it in an agreement with the finding by Younes et al study found higher levels of diabetes distress were highly correlated with depressive symptoms, with distress and depression both being significant predictors of one another individual with T1D 38 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding further aligns with prior research that found high rate of depressive symptoms individual with T1D, which were linked to their diabetes related distress 24 . Finally, it in an agreement with the finding by Younes et al study found higher levels of diabetes distress were highly correlated with depressive symptoms, with distress and depression both being significant predictors of one another individual with T1D 38 .…”
Section: Discussionsupporting
confidence: 91%
“…In the Type 1 diabetes subgroup, the relationship between diabetes distress and depression was significant and more pronounced. This suggests that individuals with Type 1 diabetes may be particularly vulnerable to the psychological consequences of diabetes distress, consistent with prior studies indicating high rates of depressive symptoms in this population 24 , 36 , 38 . The finding also in accordance with the study by Stahl-Pehe, et al that showed a significant association between diabetes distress and depression among adults with T1D 37 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…43 One study also reported that the slum adult population having diabetes shows depression related to diabetes, and some of them show suicidal ideation to get rid of their diabetes life. 44 In addition, several past studies confirm that an inactive lifestyle plays a leading role in developing T2D among the majority of the population. [41][42][43] Low socioeconomic status, low income and illiteracy are also associated with a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, patients with Nephropathy, Retinopathy, or Diabetic Foot were considered as the morbid group, whereas their criteria were broader. Sharif et al studied 504 T2DM patients in Karachi, Pakistan (21), and posited that elevated fasting blood sugar (FBS) levels, urban residence, physical disability, and limited social support are risk factors for depression and suicidal ideation. Our study found a significant link between HbA1c levels and suicidal ideation in both groups.…”
Section: Discussionmentioning
confidence: 99%